2003
DOI: 10.2174/0929867033456783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Mechanism of Sigma-1 Receptors: Towards A Hypothesis that Sigma-1 Receptors are Intracellular Amplifiers for Signal Transduction

Abstract: Although sigma receptors were discovered in 1982, the biochemical and physiological roles of sigma receptors have just begun to unveil. Sigma receptors are non-opioid, non-phencyclidine receptors that contain two subtypes: sigma-1 and sigma-2 receptors. The sigma-1 receptor has been cloned and its sequence does not resemble that of any mammalian protein. Sigma-2 receptors have not been cloned. The focus of this review will be on sigma-1 receptors. Sigma-1 receptors contain 223 amino acids and reside primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 57 publications
3
156
0
2
Order By: Relevance
“…71 This receptor, with low affinity for PCP, has been suggested to facilitate NMDA transmission. 72 The contributions of these systems, as well as others, on PCP-disrupted PPI in the OxtÀ/À mice should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…71 This receptor, with low affinity for PCP, has been suggested to facilitate NMDA transmission. 72 The contributions of these systems, as well as others, on PCP-disrupted PPI in the OxtÀ/À mice should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The sigma-1 receptor binds to endogenous neurosteroids, and its amino acid sequence is not similar to other proteins [64]. Rimcazole and BD1008, selective sigma antagonists, attenuate the lethal and epileptogenic effects of cocaine in animal models [65,66].…”
Section: Post-receptor Effects Of Cocainementioning
confidence: 99%
“…Unpublished observation of our team even revealed that the immunohistochemical distribution in adult is found similar to that observed at P15. Activation of the s 1 receptor results in an efficient regulation of intracellular Ca 2 þ concentration (Su & Hayashi, 2003), resulting rapidly in both the neuromodulation of several responses to neurotransmitters, directly at the receptor activation level or indirectly through amplification of signal transduction systems (Monnet et al, 1992;GonzalezAlvear & Werling, 1994;Su & Hayashi, 2003) and to neuroprotection Maurice et al, 1999b). At the behavioral level, no s 1 receptor agonist was ever reported to present promemory ability in control animals, even submitted to a moderately reinforced learning task.…”
Section: J Meunier Et Almentioning
confidence: 99%
“…Through such a mechanism or, putatively, via direct interactions with the membrane receptors, activation of the s 1 receptor also results in modulation of several responses to neurotransmitters (Monnet et al, 1992;Gonzalez-Alvear & Werling, 1994). The s 1 system has recently been proposed by Su & Hayashi (2003) to constitute a 'unique intracellular amplifier system for signal transduction'. This nonselective, but efficient, neuromodulation affects learning and memory processes, response to stress or depression (for reviews, Maurice et al, 1999b;.…”
Section: Introductionmentioning
confidence: 99%